Sistem Informasi Sumber Daya Manusia dalam Mendukung Perencanaan Strategis Perusahaan - Noerlina Noerlina (Bina Nusantara University, 2011)
Human resources information systems within the company is required to support the activities of senior management (executives) and as a solution to address the needs of the executives by providing the ease of information collection and decision making. The results of this research is the an information system construction which is the beneficial for the executives in decision-making and for human resources in strategic planning. Thus, precise as well as qualified executive decisions will be produced, which will ultimately increase the productivity of human resources in achieving the corporate goals.